Relationship between renal ultrasonographic, CD4 cell count and proteinuria findings in HIV infected adult patients in Jos, Nigeria - P. M., Gwom; D., Atsukwei; E. D., Eze; E. O., Igoh; E. A., Gabkwe; M. D., Adams; K. M., Rabiu; I., Ezekiel (African Journal of Medical and Health Sciences, 2023)
This study intends to describe renal sonographic outcomes in matured patients with HIV/AIDS in Plateau State capital Jos and relate the outcome with proteinuria and the subjects’ CD4 cell count. The 504 subjects were evaluated for renal ultrasound scan, CD4 cell counts and dipstick proteinuria (using Combi 10 Urinalysis strips) were obtained, and their findings recorded. Twenty-four (4.8%) of the patients had abnormal renal sonographic findings while 480 (95.2%) had normal findings. Sixteen (3.2%) out of the 24 patients with abnormal renal ultrasound had enlarged kidneys, 24 (4.8%) patients had increased renal echogenicity while 19 (3.8%) had loss of corticomedullary differentiation. One (0.2%) patient was observed to have a globular kidney. Significant proteinuria was observed in all the 24 (4.8%) patients with abnormal renal sonographic findings to suggest HIV-associated nephropathy (HIVAN) while the remaining 480 (95.2%) patients had no significant proteinuria. Hence, the prevalence of HIVAN in this study was 4.8%. Kidney size, renal echogenicity and corticomedullary differentiation correlated significantly with proteinuria count with P-values of <0.05 and r-values of 0.531, 0.610 and 0.487, respectively. Similarly, renal echogenicity correlated significantly with CD4 cellular number (p < 0.05, r = -0.540). No substantial correlation was observed between renal size and CD4 tissue quantity (p > 0.05, r = 0.084) and between corticomedullary differentiation and CD4 cell amount (p >0.05, r = 0.049). Sonographically based determination of renal size and echogenicity/echopattern combined with proteinuria are good determinants of renal parenchymal disease and may have diagnostic usefulness as a non-invasive procedure in the identification of HIVAN in HIV-positive subjects with renal disease.